Physico-chemical characteristics of Composites material Based on Sulfonated Cyclone Fibre Cellulose and Benzotriazole - Irfan Gustian; Eka Angasa; Ghufira Ghufira (Graduate Program of Syiah Kuala University, 2017)
Composites material based on sulfonated cyclone fibre cellulose (SCFC) and benzotriazole (Btri) have been prepared. Cyclone fibre cellulose (CFC) was sulfonated with trimethylsilyl chlorosulfonate (TMSCS), with high degree of sulfonation (150%). The composites material, SCFC-Btri were prepared by doping of benzotriazole in various mole ratios (0.125, 0.25 and 0.5). FTIR spectrum has confirmed the ionic interaction between sulfonic acid from sulfonated cyclone fibre cellulose and benzotriazole units. Thermogravimetric analysis (TGA) showed that the composites material was thermally stable up to 150 °C. The results showed that methanol permeability of the composite material was lower than pristine Nafion112. Activation energy obtained for the materials are 0. 106 eV, 0.144 eV and 0.137 eV for SCFC-Btri mole ratios 0.125, 0.25 and 0.5 respectively, composites material was expected to be used as raw material in the fuel cell.